HARVEST CONTROL RULES OF DEMERSAL FISHERIES IN BRONDONG WATER, LAMONGAN, EAST JAVA - Harlyan, Ledhyane Ika; Lianingrum, Yulis Dwi; Setyohadi, Daduk; Tumulyadi, Agus; Muntaha, Ali (Directorate of Research and Community Service (DRPM), 2021)
Multispecies demersal fisheries management in Brondong waters have been managed by conventional single-species approach for determining catch quota or annual allowable biological catch (ABC). This might be impractical since a multispecies fishery should be managed by a multispecies fisheries management approach. The feedback harvest control rule (HCR) is a harvest control rule that has been validated and might be applied for a multispecies fishery. The aim of this study is to compare the conventional single-species approach and the feedback HCR in order to estimate the annual ABC. In this study, the annual ABC was calculated by applying two HCRs, the conventional single-species approach that applying the Schaefer surplus production model into the catch and effort of the dominant demersal fisheries data series of 2011 – 2020. The results showed that the Schaefer model provided the annual ABC higher than the feedback HCR estimation. Therefore, it was safe to apply the feedback HCR than the Schaefer model to determine the annual ABC. Under data-limited conditions, the feedback HCR might be an option to manage multispecies fisheries.